The wisdom of polygamy in Islam: The law and customary practice in Afghanistan / Nasir Ahmad Yousefi - Ahmad Yousefi, Nasir (2017)
This paper aims to review the wisdom of polygamy in Islam, how the Prophet Muhammad (s.a.w) put it into practice by his divinely guided lifestyle and its practice in Afghanistan. Ninety nine percent of Afghanistan‘s populations are Muslims and yet women in polygamous marriages are subjected to ill-treatment - a treatment which is often sanctioned by customs and/or the decisions of the so-called Jirga (elders council). This paper explains that the polygamy related customs and the Jerga‘s decisions in Afghanistan are contrary not only to Islamic Law but also Afghanistan domestic laws and international human rights law.